2021
DOI: 10.1145/3424282
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Moderating Effect of Security Technologies on Employees Compliance with Cybersecurity Control Procedures

Abstract: The increase in cybersecurity threats and the challenges for organisations to protect their information technology assets has made adherence to organisational security control processes and procedures a critical issue that needs to be adequately addressed. Drawing insight from organisational theory literature, we develop a multi-theory model, combining the elements of the theory of planned behaviour, competing value framework, and technology—organisational and environmental theory to examine how the organisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
0
8
1
Order By: Relevance
“…Compared to the findings from other fields of study, the insignificant effect of cognitive belief was rare (e.g. Verbeke, 2005;Tolma et al, 2006;Onumo et al, 2021) but not unheard of. There are two main reasons behind this finding.…”
Section: Discussioncontrasting
confidence: 75%
“…Compared to the findings from other fields of study, the insignificant effect of cognitive belief was rare (e.g. Verbeke, 2005;Tolma et al, 2006;Onumo et al, 2021) but not unheard of. There are two main reasons behind this finding.…”
Section: Discussioncontrasting
confidence: 75%
“…Agriculture is the foundation of peace. Solving the "three rural" issues has always been the "top priority" of the work of the central government, it is necessary to conform to the development trend of global informatization, and take the agricultural Internet of ings as the core and most fundamental information technology of agricultural informatization, rmly grasp the information revolution and provide a major historical opportunity for agricultural modernization to "overtake on the curve," aim at the development direction of smart agriculture, and make up for the shortcomings [1].…”
Section: Introductionmentioning
confidence: 99%
“…In Ifinedo's (2014) research, attitude was identified as having the greatest impact on compliance intention. An individual's habits (Aigbefo et al, 2022) and cognitive beliefs (Onumo et al, 2021) also strongly influence his intention to comply with an organization's cybersecurity policy requirements. Meanwhile, behavior intention is significantly influenced by attitudes toward a particular behavior (Tam et al, 2022).…”
Section: The Developed Themes and Subthemesmentioning
confidence: 99%